Inside the FDA : - Hawthorne, Fran (John Wiley & Sons, 2005)
Inside the FDA takes a closer look at the practices, people, and politics of this crucial watchdog in light of the competing pressures and trends of modern society, revealing what the FDA is supposed to do, what it actually does-and fails to do-who it influences, and how it could better fulfill its mandate. The decisions that the FDA makes are literally life and death. Inside the FDA provides a sophisticated account of how this vitally important agency struggles to balance bureaucracy and politics with its overriding mission to promote the country's health.